1987
DOI: 10.1007/bf01656397
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function in the surgical patient

Abstract: It has long been appreciated that the cardiovascular system plays a vital role in surgical illnesses. Although attention has, historically, been largely focused on the left ventricle, it has become apparent in recent years that the right ventricle may contribute significantly to an absolute or relative failure of cardiovascular adaptation to acute and chronic disease states. Many of the physiological principles governing left ventricular function also determine right ventricular function. Thus, the right ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…These studies linked the changes to positive pressure ventilation, cardiopulmonary bypass, systemic inflammation, and increased pulmonary bed vasoconstriction by vasoactive drugs. [23][24][25] These factors are unlikely to be causative in the present findings because they mediate RV dysfunction through cavity dilation, not reduction as we demonstrated. In addition, several studies have demonstrated normalization of pulmonary vascular resistance by 48 hours after surgery, 24,25 and therefore, this would be unlikely to affect RV function 6 days after surgery.…”
Section: Effects Of Cabg On Rv Functionmentioning
confidence: 49%
“…These studies linked the changes to positive pressure ventilation, cardiopulmonary bypass, systemic inflammation, and increased pulmonary bed vasoconstriction by vasoactive drugs. [23][24][25] These factors are unlikely to be causative in the present findings because they mediate RV dysfunction through cavity dilation, not reduction as we demonstrated. In addition, several studies have demonstrated normalization of pulmonary vascular resistance by 48 hours after surgery, 24,25 and therefore, this would be unlikely to affect RV function 6 days after surgery.…”
Section: Effects Of Cabg On Rv Functionmentioning
confidence: 49%
“…In recent years, attention has been focused on the RV function and its association with morbidity and mortality. The RV is affected by changes in afterload, preload, and contractility [ 12 , 13 ]. In surgical patients, some consideration of RV function is warranted as many surgically relevant disease states may potentially alter such determinants of RV function [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scveral authors have proposed that when ARDS is complicated by elevation of pulmonary vascular resistance (PVR) , ventricular contractility is compromised and the patients' prognosis deteriorates [36] .…”
Section: Lntroductionmentioning
confidence: 99%